APPLICATION OF NEW TECHNOLOGIES TO IMPROVE THE LEARNING PROCESS - Kholida Sharipova (Social science and innovation, 2023)
The application of new technologies has revolutionized the learning process, enhancing its effectiveness and efficiency. Through the integration of virtual reality, augmented reality, artificial intelligence, and interactive platforms, learners can engage in immersive and personalized educational experiences. Virtual reality simulations enable students to explore complex concepts and environments, fostering deeper understanding and critical thinking. Augmented reality overlays digital information onto the real world, creating interactive and engaging learning opportunities. Artificial intelligence-powered systems provide personalized feedback and adaptive learning pathways, catering to individual needs. Interactive platforms facilitate collaboration and knowledge sharing among learners, fostering a dynamic and inclusive learning community. The application of these technologies holds immense potential to transform education and empower learners in the digital age.